Use of Efficient and Affordable Technologies in Checkmating the Existence of Hazardous Waste (2010)
One of the major problems impeding achieving environmentally sound management of hazardous waste (domestic, agricultural or industrial) in African countries is that there are no efficient and affordable technologies that can be adhered to. Human activities, either for production or processing lead to the production of wastes (solid, liquid or gas) which must be minimized because of their harmful effect on health of the living being and their destruction of environmental aestheticism. The technologies like rotary kiln, chemical disinfection etc, are efficient but they have not yielded the needed result. The reason is that they are not affordable. The affordable ones like brick or drum incinerator, waste burning and others result to massive emission of black smoke, fly ash and repulsive odours. All these eventually have negative effects on climate. This paper aims at promoting efficient and affordable technologies to manage hazardous waste in Ibadan, Nigeria. It provides information on the locations, types and sources of hazardous waste generated in this area and use this information to choose appropriate technologies that are affordable by the people. It is recommended that waste recycling and reuse, safe bury, waste minimization, composting and landfill technologies should be encouraged. Government at all levels should work in hand with the NGOs, community-based organizations, women, youth and public interest group programmes, in collaboration with local municipal authorities, to mobilize community support for waste reuse and recycling through focused community-level campaigns. Also, these technologies should be publicized through workshops, local meetings, and mass media to the populace for the benefit of the community and the country as a whole.